PENERAPAN METODE PROTOTYPE PADA SISTEM INFORMASI PENGOLAHAN DATA PEMANEN BERBASIS WEB DI PT. SAGO NAULI - Minarni Minarni; Deasy Rahmadany; Ganda Yoga Swara; Eva Yulianti; Dede Wira Trise Putra (Ensiklopedia of Journal, 2025)
Abstract: PT. Sago Nauli is a palm oil plantation company located in Mandailing Natal Regency. To carry out its operations, PT. Sago Nauli employs casual workers, specifically harvesters. Problems arise during the registration of harvesters, which is handled by the foreman, who then registers them with the office clerk. Data processing and income reporting are still done manually using a general ledger. Unclear time data for harvesters often leads to errors in salary calculations, as the foreman's information does not always match the harvester's data. This research aims to develop an information system for processing harvester data, from registration to income generation, using a prototype method. The system was developed using the CodeIgniter framework, the Apache web server, the MySQL database, the PHP programming language, and Bootstrap. The results indicate that the system can be used for harvester registration and provides income information to both harvesters and foremen. Additionally, foremen can validate harvester income data, and the system generates a summary report of monthly salary data for the office manager.Keywords: information systems, harvesting data, prototype.